Activity of Various Essential Oils Against Clinical Dermatophytes of Microsporum and Trichophyton - Parrish, Nicole; Fisher, Stefanie L.; Gartling, Ashlea; Craig, David; Boire, Nicholas; Khuvis, Joshua; Riedel, Stefan; Zhang, Sean (Frontiers in Cellular and Infection Microbiology, 2020)
Dermatophytoses account for nearly a quarter of all fungal infections worldwide. These difficult to treat infections of the skin, hair, and nails, are growing more resistant to conventional antifungal treatments, and when treatable, often require prolonged therapeutic regimens. For centuries, essential oils have been used to treat a variety of ailments. In this study, we evaluated the clinical effects in vitro of 65 essential oils and 21 essential oil blends against various clinical species/strains of dermatophytes from two primary genera, Microsporum and Trichophyton. Our aim: To determine the overall activity of a wide range of essential oils against a number of clinical strains of dermatophytes. For all assays, 16 clinically derived species/strains of dermatophytes were used. The activity of each essential oil was assessed using a modified disk-diffusion assay over a period of 21 days of incubation vs. standard antifungal drugs. Subsequently, we determined the minimum inhibitory dilution possible for the most potent essential oils and performed combination testing to determine if synergy could be demonstrated with sub-inhibitory concentrations. We also assessed the effect of repeated vs. single applications. Of all the essential oils tested, cassia, cilantro, cinnamon, thyme, and oregano were the most potent along with one blend, DDR Prime; all genera/species tested were completely inhibited for 21 days following a single application. Many of the other oils tested exhibited temporal differences in activity where significant inhibition was observed ≤10 days of incubation which declined by day 21. Synergistic combinations were achieved with oregano and cilantro, cassia, or cinnamon bark; rose and cassia were also synergistic. Repeat application maintained complete inhibition for citronella, lemon myrtle, and litsea out to 21 days, but not lemon grass or On Guard. More study is necessary to understand the ways essential oils inhibit the growth of dermatophytes. Comprehensive research aimed at understanding the mechanism of action of essential oils and their components may provide the basis for a natural alternative to topical antifungal drugs. Such research could be envisioned to target optimal combinations and determine the timing between applications to provide for maximum inhibition of recurrence or growth.